The Gambia : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses Poverty Reduction Strategy Paper (PRSP) 2007-11 for The Gambia. PRSP II builds on the long-term development Vision 2020 of The Gambia. It also takes cognizance of the fact that implementation of PRSP I suffered from revenue shortfalls as the IMF suspended its program with the Gambia. Consequently, PRSP II attempts to include interventions that were planned for PRSP I. PRSP II contains interventions and actions that have been well synchronized to ensure complimentarily, and the institutional and operational structures will also be streamlined to avoid duplication.